The Ramsay Hunt Syndrome in Sub-Saharan Africa: A Case Report from Benguela, Angola: Síndrome de Ramsay Hunt en África subsahariana: Reporte de caso de Benguela, Angola - Kapitão, Antonino (2025)
Ramsay Hunt syndrome (RHS) is a rare neurological complication of varicella-zoster virus infection, characterized by peripheral facial paralysis, otalgia, and auricular vesicular lesions. We report the case of a 31-year-old woman presenting with typical symptoms of the syndrome, clinically diagnosed at the General Hospital of Benguela, Angola, in a resource-limited setting. Treatment with acyclovir, prednisone, and supportive measures led to good functional recovery. This case highlights the importance of clinical recognition of RHS in regions with limited access to complementary tests, reinforcing the need for improved diagnostic surveillance and medical training. Keywords: Hunt's syndrome; Herpes Zoster Oticus; Facial Paralysis, Peripheral; Varicella Zoster Virus Infection (Source: MeSH, NLM).